A method for preparing foam copper with layered pore structure

By screening and grading the copper powder and using pressurized chunks during the sintering process, the problems of uncontrollable porosity and complex process in the existing foam copper preparation methods are solved, and the controllable porosity and improvement of foam copper performance are achieved.

CN115740450BActive Publication Date: 2025-04-08HEFEI UNIV OF TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211439483.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-11-17
Publication Date
2025-04-08
Estimated Expiration
2042-11-17

AI Technical Summary

Technical Problem

The existing foam copper preparation methods have problems such as complex process, high cost, uneven pore structure and uncontrollable porosity.

Method used

By sieving and grading the copper powder with low loose density, putting it into a crucible and placing pressurized blocks, foam copper with a layered pore structure was prepared by loose sintering.

Benefits of technology

The controllability of porosity, uniformity of pore shape and layered distribution are achieved, and the conductivity, thermal conductivity and structural stability of foam copper are improved, while reducing production costs and operational complexity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115740450B_ABST
    Figure CN115740450B_ABST
Patent Text Reader

Abstract

The present invention discloses a method for preparing a copper foam with a layered pore structure, wherein the copper powder with a low bulk density is screened, graded and evenly spread in a crucible, and a certain mass of a pressurized block is placed above the copper powder, and then sintered in a protective atmosphere, and finally a porous copper foam with layered pore distribution and controllable pore size and porosity is obtained. The method for preparing copper foam of the present invention has the advantages of simple process, low cost, high product shape and size accuracy and controllable porosity, and the porosity of the obtained copper foam can be regulated in a wide range of 30% to 70% volume ratio, and the shape of the pores is flat. The copper foam with the above-mentioned pore characteristics has good application prospects in the fields of lithium battery electrodes, catalyst carriers, etc.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for preparing foam copper with a layered pore structure, and belongs to the technical field of porous metal material preparation. Background Art

[0002] Copper foam is a new multifunctional material with a large number of connected or unconnected pores evenly distributed in a copper matrix. While retaining the ductility, electrical conductivity and thermal conductivity of metallic copper, it also has the advantages of low density, high porosity, large specific surface area and good chemical stability. It has broad application prospects in the fields of filtration, catalysis, sensing and energy. At present, the main methods for preparing copper foam include electrodeposition, directional solidification and dealloying, but these methods still have certain shortcomings. For example, Du et al. prepared lotus-shaped copper foam by directional solidification. The pore size of the sample gradually decreased from the inside to the outside and the porosity gradually increased. However, the porosity and open porosity of the obtained copper foam were relatively low, and the pore distribution was uneven (Du H, Qi J, Du S, et al. Structure and oil retaining capacity of gasar copper fabricated by radial solidification with a combined crystallizer [J]. Journal of Materials Processing Technology, 2010, 210 (11): 1523-1528.). Liu H et al. used the dealloying method to prepare copper foam with a pore size of 0.5 to 3.5 μm. The preparation method is relatively complicated, the porosity is uncontrollable, and the pore structure is relatively simple (Liu H, Wang E, Zhang Q, et al. Unique 3D nanoporous / macroporous structure Cu current collector for dendrite-free lithium deposition [J]. Energy Storage Materials, 2019, 17: 253-259.). In general, most of the current methods for preparing copper foam have problems such as complex process, high equipment requirements, high cost, uneven pore structure and uncontrollable porosity.

[0003] The loose sintering method is one of the powder metallurgy sintering technologies. It refers to the process of sintering metal powder in a loose state in a fixed structure mold. Through sintering between powder particles, a certain porosity is naturally formed in the sintered body. However, the samples prepared by the traditional loose sintering method have shortcomings such as small and uneven pore size, irregular pore shape, and low porosity. Summary of the invention

[0004] In view of the deficiencies of the above-mentioned existing technologies, the present invention provides a preparation method of copper foam with flat pores distributed in layers, which is reasonable in design, simple in process, convenient in operation steps and low in production cost. The method screens, classifies and grades copper powder with low loose density, then places it in a crucible, places a pressure block with a certain mass above the powder, and finally obtains copper foam with flat pores distributed in layers through sintering.

[0005] To achieve the purpose, the present invention adopts the following technical solutions:

[0006] A preparation method of copper foam with a layered pore structure is characterized by the following steps:

[0007] Step 1: Screen, classify and grade copper powder with low loose density to obtain copper powder with a certain particle size grading.

[0008] Step 2: Evenly spread the graded copper powder in a crucible, and place a pressure block with a flat surface above the copper powder.

[0009] Step 3: Place the crucible filled with copper powder into a tube furnace, sinter in a protective atmosphere, and remove it from the tube furnace after cooling to obtain copper foam with a layered pore structure.

[0010] Further, in step 1, the copper powder is produced by electrolysis or water atomization and other methods, has a dendritic or other irregular shape, and its loose density is 0.5 - 1.4 g / cm 3 .

[0011] Further, in step 1, the screening and grading is to pass the copper powder through sieves with mesh numbers a and b in sequence (where the range of a is 100 - 500 meshes, the range of b is 300 - 800 meshes, and a < b), take the oversize powder on the sieve with mesh number b, obtain copper powder with a particle size range between -a and +b meshes and mix it evenly. For example, pass through sieves with mesh numbers 200 and 300 in sequence, take the oversize powder on the 300-mesh sieve to obtain copper powder with a particle size of 200 - 300 meshes; pass through sieves with mesh numbers 300 and 400 in sequence, take the oversize powder on the 400-mesh sieve to obtain copper powder with a particle size of 300 - 400 meshes, and so on.

[0012] Further, in step 1, the grading is to control the porosity and pore shape, mix copper powders with different particle size ranges (such as mixing copper powders with particle sizes of 200 - 300 meshes and 300 - 400 meshes evenly) to obtain copper powder with a certain particle size grading.

[0013] Further, in step 2, the crucible is a high-temperature-resistant alumina crucible or graphite crucible, and the shape is not limited.

[0014] Furthermore, in step 2, a method of placing a flat-surface pressure block on the copper powder is as follows: a layer of carbon paper is laid flat on the loose copper powder in the crucible, and a copper plate or iron plate with a surface flatness of 50 to 1000 g is loaded on the carbon paper, and the specific mass is adjusted according to the amount of loose sintered copper powder. The function of the pressure block is to subject the loose powder to a certain pressure in the direction of gravity during the sintering process, thereby promoting shrinkage in this direction, which is conducive to the formation of lamellar pores.

[0015] Furthermore, in step 3, the sintering temperature is 600° C. to 850° C. and the holding time is 1 to 2 hours.

[0016] Furthermore, in step 3, the protective atmosphere is hydrogen, nitrogen, argon and a mixture thereof.

[0017] The porosity distribution range of the foam copper obtained by the invention is 30% to 70%.

[0018] The present invention is based on the traditional loose sintering process, by regulating the particle size distribution of the raw copper powder and placing a pressure block above the loosely paved powder, a gravity field is formed during the sintering process, and the displacement and pore formation of the particles during the sintering process are controlled, and a foam copper with flat pores distributed in layers is obtained. The advantages of this pore structure, such as high specific surface area and high uniformity, are key factors for maintaining the electrical conductivity, thermal conductivity and structural stability of the foam copper. At the same time, the process has the characteristics of low cost and simple operation. The lower the loose density of the raw copper powder used in the method, the looser the powder particles are when naturally piled up, the higher the initial porosity, and the porosity of the final product is also improved, so the copper powder with low loose density is used to prepare a foam copper sample with high porosity.

[0019] The beneficial effects of the present invention are embodied in:

[0020] 1. The method for preparing copper foam of the present invention has the advantages of simple process, low cost, high precision of product shape and size, and controllable porosity. The porosity of the obtained copper foam can be regulated in a wide range of 30% to 70% by volume, and the shape of the pores is flat. The copper foam with the above-mentioned pore characteristics has good application prospects in the fields of lithium battery electrodes, catalyst carriers, etc.

[0021] 2. The method for preparing copper foam of the present invention improves the stability, distribution uniformity and specific surface area of ​​the pore shape in the sintered body, and can effectively improve the electrical conductivity, thermal conductivity and high structural stability of the copper foam.

[0022] 3. The present invention uses low bulk density copper powder as raw material to prepare foamed copper, and the raw material is low in cost and easy to obtain. After the low bulk density copper powder with small particle size is pressurized, it can be sintered at a relatively low temperature to prepare foamed copper with high porosity and flat pores distributed in layers, and the porosity can be regulated and the ideal layered structure can be obtained by controlling the sintering process. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 It is a schematic diagram of placing a pressure block above the copper powder in the present invention;

[0024] Figure 2 A schematic diagram of a copper foam having a layered pore structure prepared in the present invention;

[0025] Figure 3 This is a scanning electron microscope photograph of the microstructure of the copper foam sample prepared in Example 1;

[0026] Figure 4 This is a scanning electron microscope photograph of the microstructure of the foam copper sample prepared in Example 2;

[0027] Figure 5 This is a scanning electron microscope photograph of the microstructure of the copper foam sample prepared in Example 3;

[0028] Figure 6 This is a scanning electron microscope photograph of the microstructure of the foam copper sample prepared in Example 4. DETAILED DESCRIPTION

[0029] The following is a detailed description of an embodiment of the present invention. This embodiment is implemented on the premise of the technical solution of the present invention, and a detailed implementation method and a specific operation process are given, but the protection scope of the present invention is not limited to the following embodiment.

[0030] Example 1

[0031] A method for preparing a copper foam with a layered pore structure, the specific steps of which are as follows:

[0032] Step 1: Weigh 50 g of dendritic low bulk density pure copper powder (with a bulk density of 1.40 g / cm 3 ), and sieved through a 200-mesh sieve and a 300-mesh sieve in turn, and the powder on the 300-mesh sieve was taken to obtain a low bulk density pure copper powder with a particle size of -200 to +300 mesh.

[0033] Step 2: Weigh 20 g of the screened electrolytic copper powder and put it into a rectangular alumina crucible (15 mm × 20 mm × 10 mm), spread a layer of carbon paper on the loose copper powder in the crucible, and place a copper plate with a mass of 150 g on the carbon paper.

[0034] Step 3: Place the crucible in a tubular sintering furnace, heat to 750° C. at a heating rate of 5° C. / min under hydrogen protection, and sinter for 2 h to obtain a copper foam with flat pores distributed in layers.

[0035] The foamed copper sample prepared in this embodiment was subjected to microstructure test and porosity test. The foamed copper prepared in this embodiment using low bulk density electrolytic copper powder as raw material powder had a porosity of 55.52%. Figure 3 : is a scanning electron microscope photo of the microstructure of the foam copper sample prepared in this embodiment. Figure 3 It can be seen that the sintered body has a porous structure, and the pores therein are flat in shape, and the pores form a layered distribution in the foamed copper.

[0036] Example 2

[0037] A method for preparing a copper foam having a layered pore structure, the specific steps of which are as follows:

[0038] Step 1: Weigh 50 g of low bulk density copper powder prepared by water atomization (its bulk density is 1.25 g / cm 3 ), and sieved through a 200-mesh sieve and a 300-mesh sieve in turn, taking the sieved powder on the 300-mesh sieve to obtain a low loose density pure copper powder with a particle size of -200 to +300 mesh.

[0039] Step 2: Weigh 10 g of the screened copper powder and put it into a Φ30 mm × 5 mm cylindrical alumina crucible. Place a layer of carbon paper on top of the loosely packed copper powder in the crucible, and place a copper plate with a mass of 100 g on top of the carbon paper.

[0040] Step 3: Place the crucible in a tubular sintering furnace, heat to 650° C. at a heating rate of 5° C. / min under hydrogen protection, and sinter for 2 h to obtain a copper foam with flat pores distributed in layers.

[0041] The foam copper sample prepared in this embodiment was subjected to microstructure test and porosity test. The foam copper prepared in this embodiment using water-atomized copper powder with low bulk density as raw material powder had a porosity of 45.13% and uniform pore size. Figure 4 is a scanning electron microscope photograph of the microstructure of the foam copper sample prepared in this embodiment. Figure 4 It can be seen that most of the pores are connected, the shape of the pores is flat, and they are distributed in layers in three-dimensional space.

[0042] Example 3

[0043] A method for preparing a copper foam with a layered pore structure, the specific steps of which are as follows:

[0044] Step 1: weigh 50 g of dendritic low bulk density pure copper powder (bulk density is 0.9 g / cm 3 ), and sieved through a 300-mesh sieve and a 400-mesh sieve in turn, taking the sieved powder on the 400-mesh sieve to obtain a low loose density pure copper powder with a particle size of -300 to +400 mesh.

[0045] Step 2: Weigh 10 g of the screened electrolytic copper powder and spread it in a cubic alumina crucible (20 mm × 20 mm × 20 mm), spread a layer of carbon paper on top of the loosely packed pure copper powder in the crucible, and place a copper plate with a mass of 600 g on top of the carbon paper.

[0046] Step 3: Place the alumina crucible in a tubular sintering furnace, heat to 800°C at a heating rate of 5°C / min under hydrogen protection and keep warm for 2 hours, and finally obtain foamed copper with flat pores distributed in layers.

[0047] The foam copper sample prepared in this embodiment was subjected to morphology test and porosity test. In this embodiment, low bulk density electrolytic pure copper powder was used as raw material powder to prepare the foam copper, with a porosity of 40.68% and uniform pore size. Figure 5 is a scanning electron microscope photograph of the microstructure of the foam copper sample prepared in this embodiment. It can be seen from the figure that the pore shape becomes flatter as the pressure of the pressurized block increases, the particles are arranged more closely, the number of connected pores decreases, but the pores are still distributed in layers.

[0048] Example 4

[0049] A method for preparing a copper foam with a layered pore structure, the specific steps of which are as follows:

[0050] Step 1: weigh 50 g of low bulk density copper powder prepared by water atomization method (its bulk density is 0.7 g / cm 3 ) Screening is performed sequentially through a 200 mesh screen, a 300 mesh screen and a 400 mesh screen, and the sieved powder on the 300 mesh screen and the sieved powder on the 400 mesh screen are taken to obtain copper powder with a particle size of -200 to +300 mesh and -300 to +400 mesh. The copper powder of -200 to +300 mesh and the copper powder of -300 to +400 mesh are graded according to a mass fraction of 40%:60% and mixed evenly.

[0051] Step 2: Weigh 10 g of the sieved copper powder and put it into a rectangular alumina crucible (25 mm × 15 mm × 10 mm), spread a layer of carbon paper on the loosely packed copper powder in the crucible, and place a copper plate with a mass of 500 g on the carbon paper.

[0052] Step 3: Place the alumina crucible in a tubular sintering furnace, heat to 700°C at a heating rate of 5°C / min under hydrogen protection and keep warm for 2 hours, and finally obtain foamed copper with flat pores distributed in layers.

[0053] The foam copper sample prepared in this embodiment was subjected to morphology test and porosity test. In this embodiment, water-atomized copper powder with low bulk density was used as raw material powder to prepare the foam copper, with a porosity of 35.45% and uniform pore size. Figure 6 is a scanning electron microscope photograph of the microstructure of the foam copper sample prepared in this embodiment. It can be seen from the figure that most of the pores are in a connected state, and the pore shape becomes flatter as the pressure of the pressure block increases, but maintains a layered distribution.

[0054] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a copper foam having a layered pore structure, characterized in that: Proceed as follows: Step 1, after screening, grading and grading the copper powder with low bulk density, copper powder with a certain particle size distribution is obtained; Step 2, evenly spread the graded copper powder in the crucible, and place a pressure block with a flat surface on top of the copper powder; Step 3: Place the crucible containing the copper powder into a tube furnace, sinter it in a protective atmosphere, and remove it from the tube furnace after cooling to obtain a foamed copper with a layered pore structure.

2. The method for preparing a copper foam having a layered pore structure according to claim 1, characterized in that: In step 1, the bulk density of the copper powder is 0.5 to 1.4 g / cm 3 .

3. The method for preparing a copper foam having a layered pore structure according to claim 1, characterized in that: In step 1, the sieving and grading is to sequentially pass the copper powder through sieves with mesh numbers a and b, take the sieve powder on the sieve with mesh number b, and obtain the copper powder with a particle size range of -a to +b mesh; wherein a ranges from 100 to 500 mesh, b ranges from 300 to 1000 mesh, and a <b。 4. The method for preparing a copper foam having a layered pore structure according to claim 3, characterized in that: In step 1, the grading is to control the porosity and pore shape, and copper powders of one or more particle size ranges are mixed to obtain copper powders of a certain particle size gradation.

5. The method for preparing a copper foam having a layered pore structure according to claim 1, characterized in that: In step 2, the crucible is an alumina crucible or a graphite crucible.

6. The method for preparing a copper foam having a layered pore structure according to claim 1, characterized in that: In step 2, a layer of carbon paper is laid between the copper powder and the pressure block for isolation. The pressure block is a copper plate or iron plate with a mass of 50 to 1000 g, and the specific mass is adjusted according to the amount of copper powder.

7. The method for preparing a copper foam having a layered pore structure according to claim 1, characterized in that: In step 3, the sintering temperature is 600° C. to 850° C. and the holding time is 1 to 2 hours.

8. The method for preparing a copper foam having a layered pore structure according to claim 1, characterized in that: In step 3, the protective atmosphere is hydrogen, nitrogen, argon and a mixture thereof.

Citation Information

Patent Citations

  • Preparation method of medical porous metal material with doublet hole structure

    CN102690967A

  • Preparation method of porous nano metal with controllable porosity

    CN108326306A